Stable Sheaves on a Smooth Quadric Surface with Linear Hilbert Bipolynomials - Edoardo Ballico; Sukmoon Huh (The Scientific World Journal)
We investigate the moduli spaces of stable sheaves on a smooth quadric surface with linear Hilbert bipolynomial in some special cases and describe their geometry in terms of the locally free resolution of the sheaves.